Massive endocytosis mechanisms are involved in uptake of HIV-1 particles by monocyte-derived dendritic cells - Laguía, Fernando; Chojnacki, Jakub; Erkizia, Itziar; Geli, María Isabel; Enrich, Carlos; Martinez-Picado, Javier; Resa-Infante, Patricia (Frontiers in Immunology, 2025)
IntroductionHIV-1 exploits dendritic cells (DCs) to spread throughout the body via specific recognition of gangliosides present on the viral envelope by the CD169/Siglec-1 membrane receptor. This interaction triggers the internalization of HIV-1 within a structure known as the sac-like compartment. While the mechanism underlying sac-like compartment formation remains elusive, prior research indicates that the process is clathrin-independent and cell membrane cholesterol–dependent and involves transient disruption of cortical actin. Here, we investigate the potential involvement of massive endocytosis (MEND) in this process.MethodsWe used live cell confocal imaging to measure the dimensions and dynamics of the compartment. We assessed the role of actin and cholesterol in fixed and live cells using confocal microscopy and evaluated the effect of PI3K and protein palmytoilation inhibitors during viral uptake.ResultsOur data demonstrate extensive plasma membrane invagination based on sac-like compartment dimensions (2.9 μm in diameter and 20 μm3 in volume). We showed that the cholesterol concentration doubles within the regions of viral uptake, suggesting lipid-phase separation, and that development of the sac-like compartment is accompanied by transient depolarization of cortical actin. Moreover, we observed that protein palmitoylation and PI3K inhibition reduce the sac-like compartment formation rate from 70% to 20% and 40%, respectively.ConclusionsOur results indicate the involvement of MEND mechanisms during sac-like compartment formation.